The age of high (tech) anxiety. - McFedries, P.
We live in times that some are calling The Age of Anxiety. A big chunk of our stress portfolios is taken up by modern technologies. As proof, there are many new words that people and professionals are using to describe this modern state of mind. This article briefly describes the new words and phrases and their meanings including:techno-stress, technology-related anxiety, computer rage, information fatigue syndrome, and e-mail fatigue.
Keywords: Age of Anxiety; Computer rage; E-mail fatigue; Information fatigue syndrome; Modern technologies; Techno-stress.; Technology-related anxiety